T-cell-specific Sel1L deletion exacerbates EAE by promoting Th1/Th17-cell differentiation. (September 2022) - Yao, Xue; Wu, Yi; Xiao, Tengfei; Zhao, Chuanxiang; Gao, Fengwei; Liu, Shuo; Tao, Zehua; Jiang, Yalan; Chen, Shaodan; Ye, Jun; Chen, Hua; Long, Qiaoming; et al.
Abstract: Multiple sclerosis (MS) and experimental autoimmune encephalomyelitis (EAE) are demyelinating neuroinflammatory diseases identified by the accumulation and aggregation of misfolded proteins in the brain. The Sel1L-Hrd1 complex comprising endoplasmic reticulum associated degradation (ERAD) is an ER-protein quality control system (ERQC) in the cell. Unfortunately, the contribution of ERAD to the development of these diseases has not been well explored. In this study, we used mice with a conditional deletion (KO) of Sel1L in T cells to dissect the role of ERAD on T cells and its contribution to the development of EAE. The results showed that Sel1L KO mice developed more severe EAE than the control wild type (WT) mice. Although, no obvious effects on peripheral T cells in steady state, more CD44-CD25+ double-negative stage 3 (DN3) cells were detected in the thymus. Moreover, Sel1L deficiency promoted the differentiation of Th1 and Th17 cells and upregulated the proliferation and apoptosis of CD4 T cells in vitro . Regarding the mechanism analyzed by RNA sequencing, 437 downregulated genes and 271 upregulated genes were detected in Sel1L deletion CD4 T cells, which covered the activation, proliferation, differentiation and apoptosis of these T cells. Thus, this study declared that the dysfunction of Sel1L in ERAD in T cells exacerbated the severity of EAE and indicated the important role of ERQC in maintaining immune homeostasis in the central nervous system. Highlights: The activity of ERQC is up-regulated in activated CD4 T cells. Sel1L deficiency exacerbates the development of EAE. Sel1L deficiency preferentially induced the differentiation of Th1/Th17 cells. Sel1L deficiency promotes the proliferation and apoptosis of CD4 T cells.